Exercising a right for benefits: issues of application practice - Кучма, Ольга Леонідівна (Державний вищий навчальний заклад "Запорізький національний університет", 2013)
The article analyzes documents confirming a disabled person’s right for benefits, conditions of its obtaining. A special attention is paid to gaps in law concerning the issue of documents confirming a right for benefits for disabled persons; proposals are made on current law improvement in the field studied. Thus, in particular, it is established that the documents giving a possibility for disabled person to exercise a right for benefits under current law are the following: certificate confirming relevant status, pension certificate or certificate confirming granting of social allowance in accordance with laws of Ukraine “On State Social Allowance for Disabled Persons since Childhood and Disabled Children”, “On State Social Allowance for Persons Without a Right for Pension as Well as for Disabled Persons” where a group and a ground for pension (for adults), “disabled child” category (for children) as well as their main nosologic disease forms are mentioned in relative cases (as for vision, hearing and lesion of locomotor apparatus). Certificates given to the disabled persons, in particular, certificates of common disease with their status mentioned are both the certificates of pension recipient due to disability and certificate of disability allowance recipient. The law does not stipulate the issue of certificate confirming disabled person status for person who has disability group and does not obtain disability allowance. This way, lawmaker has given an opportunity for a disabled person to exercise a right for benefits only after his exercising a right for pension or allowance receipt because a person can receive pension certificate or allowance recipient certificate after application to the relative authority for pension or allowance receipt; and certificate data prove that disabled person has exercised a right for pension or allowance receipt. How can disabled person who does not obtain pension or allowance (for example, a person does not have necessary insurance payment period for disabled person pension receipt and he does not belong to low-income group to receive disabled person allowance) and who does not have such certificate accordingly exercise a right for benefits? Based on content of Article 4, law of Ukraine “On Basics of Disabled Person Social Protection in Ukraine”, such person cannot use his right for benefits stipulated for disabled persons despite of the fact that he is disabled person himself. The author believes that such approach of lawmaker limits a disabled person in his exercising a right for benefits because the law stipulates benefits for disabled persons but not for disabled person pension or allowance recipient. Thus, the document for confirmation of disabled person’s right for benefits must be the document that confirms disabled person status independent from his exercising or not exercising other right in connection with his status (for example, connected with disabled person pension receipt). In addition, incompliance of Paragraph 3, Article 4, law of Ukraine “On Basics of Disabled Person Social Protection in Ukraine” (where certificate provision is considered to be a confirmation of disabled person status) with other norms is in the fact that other documents, except certificate, must be submitted to obtain a right for benefits depending on the benefit that disabled person would like to use. For example, to obtain a right for use of free of charge parking place for a transport vehicle, a disabled person must submit according to his registered place of residence to district labor and social people protection authority, among others, the following documents: original and copy of disabled person pension certificate or certificate state social allowance recipient that is paid instead of pension containing the record on disability due to locomotor apparatus lesion; original and copy of a transport vehicle registration certificate; original and copy of the certificate for the right of transport vehicle driving of a relevant category. The author proposes to amend to the law giving a right to a disabled person to obtain benefits on the base of MSEC reference or/and other documents.

У статті аналізуються документи, які підтверджують право інваліда на пільги, умови їх отримання, акцентовано увагу на прогалинах у законодавстві щодо видачі інвалідам документів, які підтверджують право на пільги, внесені пропозиції по удосконаленню чинного законодавства в досліджуваній сфері
Реалізація права інваліда на пільги: проблеми практики застосування
Keywords: пільги інваліда; документи; які підтверджують право на пільги; статус інваліда; повноваження МСЕК; disabled person’s benefits; documents that prove the right for benefits; disabled person’s status; powers of MSEC